13th Annual IEEE/SEMI Advanced Semiconductor Manufacturing Conference. Advancing the Science and Technology of Semiconductor Ma
DOI: 10.1109/asmc.2002.1001567
|View full text |Cite
|
Sign up to set email alerts
|

A robust shallow trench isolation (STI) with SiN pull-back process for advanced DRAM technology

Abstract: In this paper, the effect of SiN pull-back process for shallow trench isolation (STI) is investigated by measuring DRAM array's refresh time (Tref) and yield as sensitive monitors. The SiN pull-back is performed by using H3P04 solution after trench etch (i.e. before liner oxidation). For comparison, DRAMS were fabricated by using various isolation methods including LOCOS, conventional STI, and poly-buffered STI (PB-STI). The SiN pull-back process is known for reducing "divot" around the top corner in conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Shallow Trench Isolation(STI) is a device isolation technique for integrated circuits. As the semiconductor industry moved to sub 0.25um CMOS technology there is a need for creating very small void free gaps on the wafer sub-layer [1,2,3,4] . STI is a mainstream isolation method for advanced logic, DRAM, SRAM and flash memory.…”
Section: Introductionmentioning
confidence: 99%
“…Shallow Trench Isolation(STI) is a device isolation technique for integrated circuits. As the semiconductor industry moved to sub 0.25um CMOS technology there is a need for creating very small void free gaps on the wafer sub-layer [1,2,3,4] . STI is a mainstream isolation method for advanced logic, DRAM, SRAM and flash memory.…”
Section: Introductionmentioning
confidence: 99%
“…These can result in the inverse narrow width effect (INWE), gate oxide integrity (GOI) degradation, extra subthreshold leakage and power dissipation. Among the recent reports on the suppression of subthreshold kinks [4][5][6][7][8], large tilted sidewall boron implantation [4] seems to be easily manufacturable. However, this process involves extra lithography to avoid the impact on the p-channel MOS region.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al have reported using a nitric oxideannealed sidewall to suppress boron out diffusion [5], but simultaneously introduce latent GOI risk due to the slow oxidation rate on the nitrided silicon surface. Although other methods based on active corner engineering [6][7][8] show an improved performance, they all seem to have a downscaling limitation, because in the liner oxidation step the active width of narrow devices cannot be well controlled. Although the kink effect has been widely investigated and effectively eliminated in standard CMOSFETs, the subthreshold characteristics of LDMOSFETs have not been well studied.…”
Section: Introductionmentioning
confidence: 99%